Brainstem Stroke From Rare Case of Foville Syndrome - Kevin Aldenio Hatma Krista; Rizaldy Taslim Pinzon; Kehat Dowie Setiabudi Arrung; John Kelvin Bastian Dowansiba (Universitas Pelita Harapan, 2026)
Introduction: Foville syndrome is a rare neurological syndrome resulting from infarction in the perforating branches of the basilar artery, involving the nuclei of cranial nerves VI and VII and the corticospinal tract. It is clinically characterized by ipsilateral horizontal gaze palsy, ipsilateral peripheral facial paralysis, and contralateral hemiparesis. Its rarity often poses diagnostic challenges in clinical practice. Case Presentation: A 54-year-old woman presented with sudden diplopia and right-sided weakness for 16 hours. She had a history of controlled hypertension and diabetes mellitus. Neurological examination revealed left horizontal gaze palsy, left peripheral facial weakness, and right hemiparesis (muscle strength 2/5). Brain CT showed pontine infarction with severe basilar artery stenosis. The patient was treated with dual antiplatelet therapy, high-intensity statin, and supportive therapy including eye patching and physiotherapy. She was discharged after 8 days with moderate disability (mRS 3) and showed improvement to mild disability at 3-month follow-up. Discussion: Foville syndrome results from lesions in the pontine tegmentum involving the abducens nucleus, facial nerve fibers, and corticospinal tract. It is commonly caused by ischemic infarction due to atherosclerotic basilar artery disease. Clinical findings in this case align with the classic triad. Management depends on onset time; thrombolysis was not indicated due to delayed presentation. Dual antiplatelet therapy and risk factor control remain the mainstay treatment. Conclusions: We report a rare case of Foville syndrome that arises as a result of an infarction stroke affecting the pons. Keywords: Basilar Artery Stenosis, Brainstem Stroke, Foville Syndrome, Pontine Infarction